(untitled) (Minerva, 2019)
This paper eonsists on a typologieal analysis of laryngeal phonems: glottals, pharyngeals and, partly, uvulars, in order to identify the real nature of the three PIE laryngeals. As a first attempt, we propose /?/, /h/ and /hw/, a hypothesis based merely on the statistical probability of these phonems in a corpus of ea. 300 languages. Inasmuch as the more noticeable feature of the PIE laryngeals is the influence on adjacent vowels, we analyze the relation between vowels and laryngeals in arabic, hebrew, arbore and other languages.